The world according to Xi everything you need to know about new China - Brown, Kerry 1967- (I. B. Tauris & Co. Ltd, 2018)
China is now the most powerful country on earth. Its manufacturing underpins the world's economyl its military is growing at the fastest rate of any nation and its leader--Xi Jinping--is to set the pace an and tone of world affairs for decades. In 2017 Xi Jinping became part of the constitution--an honour not seen since Chairman Mao. Here, China expert Kerry Brown guides us through the world according to Xi: his plans to make China the most powerful country on earth and to eradicate poverty for its citizens. In this captivating book we discover Xi's beliefs, how he thinks about communism, and how far he is willing to go to defend it--back cover